1989
DOI: 10.1002/1097-0142(19890201)63:3<440::aid-cncr2820630308>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for relapse after complete response in patients with metastatic germ cell tumors

Abstract: Among 216 patients with metastatic germ cell tumors who achieved a complete response (CR) to cisplatin-based chemotherapy (CT), 38 have experienced a relapse. Prognostic factors for time to relapse from time of response were considered using the Cox proportional hazards model. Compared with patients who responded to CT and did not require surgery and patients whose surgery showed only either necrotic debris or mature teratoma, those who required surgery for residual tumor after CT were at much higher risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Incompletely resected patients had a poor prognosis (5y-RF%:50%), as was found in other studies (Tait et al, 1984;Harding et al, 1989;Jansen et al, 1991). (Harding et al, 1989), but in contrast with the observations in several other studies (Tait et al, 1984;Geller et al, 1989;Jansen et al, 1991;Mead et al, 1992). The observation in our study may be explained by lack of power to detect an existing difference due to the relatively low number of relapses.…”
Section: Discussionmentioning
confidence: 48%
“…Incompletely resected patients had a poor prognosis (5y-RF%:50%), as was found in other studies (Tait et al, 1984;Harding et al, 1989;Jansen et al, 1991). (Harding et al, 1989), but in contrast with the observations in several other studies (Tait et al, 1984;Geller et al, 1989;Jansen et al, 1991;Mead et al, 1992). The observation in our study may be explained by lack of power to detect an existing difference due to the relatively low number of relapses.…”
Section: Discussionmentioning
confidence: 48%
“…16, [21][22][23][24] In the adult population, tumor marker decline has been shown to be an independent predictor of prognosis after the start of therapy, indicating patients for whom a more aggressive treatment strategy should be considered. 16, [21][22][23][24] In the adult population, tumor marker decline has been shown to be an independent predictor of prognosis after the start of therapy, indicating patients for whom a more aggressive treatment strategy should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Geller et al at Memorial Sloan Kettering Cancer Center [5] reported on prognostic factors for relapse in 216 patients who had complete responses to cisplatin-based chemotherapy. Viable NSGCT in postchemotherapy resection specimens was associated with the highest risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…The initial report by Einhorn et al [10] acknowledged the poor prognosis and high risk of relapse in patients with viable NSGCT in resections performed after primary chemotherapy and suggested that these patients would benefit from additional chemotherapy. Stoter et al [14] and Geller et al [5] have advocated this approach on the basis of their experience with 17 and 18 patients, respectively. Other investigators have similarly advocated postoperative chemotherapy [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation